2014
DOI: 10.1039/c4em00224e
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of carboxylated carbon nanotubes and the corresponding variation in their colloidal behavior

Abstract: Length dependent dispersibility of carboxylated multi-walled carbon nanotubes is presented using a novel approach where a batch of carboxylated nanotubes was size sorted via ultracentrifugation into different fractions with lengths ranging from 150 to 950 nm. The different fractions had the same tube diameter and degree of oxidation. The dispersibility of the nanotube fractions showed dependence on the length where the longer tubes showed more aggregation in terms of larger particle size, zeta potential and lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
1
0
1
Order By: Relevance
“…2 and Table 2 ). The shorter MWCNTs showed a larger Zeta potential compared with the longer ones, which could be due to different dispersibility of MWCNTs contributed by the lengths as suggested before [ 26 , 27 ]. The results indicated that the toxicity of MWCNTs was length dependent that exposure to longer MWCNTs was associated with more morphological changes of HUVECs (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…2 and Table 2 ). The shorter MWCNTs showed a larger Zeta potential compared with the longer ones, which could be due to different dispersibility of MWCNTs contributed by the lengths as suggested before [ 26 , 27 ]. The results indicated that the toxicity of MWCNTs was length dependent that exposure to longer MWCNTs was associated with more morphological changes of HUVECs (Fig.…”
Section: Discussionmentioning
confidence: 65%
“…Bu nedenle ilgili çalışma kapsamında, artan nanomateryal kullanımına karşı karbon nanotüplerin (SWCNT, MWCNT ve CCNT) arpa çimlenmesi üzerinde olası etkileri araştırılmıştır. Çalışma kapsamında değerlendirilen karbon nanotüplerin fizikokimyasal özelliklerinin, bu yapıların bulundukları ortamdaki hareketlerini etkilediği, ortam koşullarına verdikleri cevabı değiştirdiği yapılan çalışmalar ile gözlenmiştir(24).…”
unclassified